Nanotechnologies and food. Volume I: report - UK. Parliament. House of Lords (London, 2010)
"People are understandably sensitive about changes to the food that they eat. In the past the introduction of novel technologies in the food sector has sometimes met with resistance or even hostility. The public's attitude toward food is influenced by a number of considerations including a fear of novel risks, the level of trust in the effectiveness of regulation, and other wider social and psychological factors (shaped by views on health, the environment and science). The development of nanotechnologies in the food sector may well elicit some of these concerns. However, as many new technologies have in the past, they may offer consumers and society a number of benefits. We launched this inquiry into the use of nanotechnologies in the food sector to investigate whether nanotechnologies may indeed play a valuable role in the food sector, whether effective systems are in place to ensure that consumers are aware of and protected against any potential risks, and to understand and address some of the concerns that the public may have about these new technologies.